Trends in Implementing the Make a Match Learning Model in Improving Science Learning Outcomes in Indonesian Elementary Schools: A Systematic Literature Review - Riana Safitri; Rohmani Rohmani (Institute of Multidisciplinary Research and Community Service, 2026)
This study aims to analyze the implementation trends of the Make a Match learning model in improving science learning outcomes among Indonesian elementary school students and to identify challenges and opportunities for its implementation in the digital era. This study used a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol to ensure a systematic, transparent, and replicable process. A literature search was conducted through Google Scholar and GARUDA databases for publications from 2021–2025 using the keywords “Make a Match,” “learning outcomes,” “science,” and “elementary school.” A total of 2,789 articles were initially identified, and after title screening, duplicate removal, abstract evaluation, and full-text assessment, 10 articles met the inclusion criteria and were further analyzed. Data extraction focused on the study design, sample characteristics, learning media, and students' cognitive, affective, and psychomotor learning outcomes. The quality of the studies was assessed using the Mixed Methods Appraisal Tool (MMAT), which showed that most of the selected studies were categorized as high quality. The findings indicate that the Make a Match learning model consistently improves elementary school students' science learning outcomes. The results indicate that the Make a Match model contributes to improving science students' learning outcomes, with consistent positive trends observed across the reviewed studies. However, 90% of the reviewed studies still relied on conventional learning media such as physical cards and manual flashcards. Only one study explicitly integrated interactive digital electronic modules into the learning process. These findings indicate the need for further innovation in technology-based Make a Match learning models to support digital-generation learners in contemporary elementary education. Keywords: Make a Match, Learning Outcomes, Elementary School Science.